2022
DOI: 10.1177/03611981221108380
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Travel Time Reliability on Interstates Using Linear Quantile Mixed Models

Abstract: Under the Moving Ahead for Progress in the 21st Century Act (MAP-21), state Departments of Transportation (DOTs) are responsible for reporting travel time reliability and also setting targets and showing progress toward those targets. To know how to improve travel time reliability and what to expect from investments in transportation infrastructure, state DOTs need a better understanding of the factors that affect travel time reliability and methods to predict future travel time reliability. This paper propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This split could help evaluate model flexibility. GRF and QRF models were created for freeway and interchange segments separately because a previous study found the independent variables could affect these two types of segments differently ( 26 ). The 50th, 80th and 90th percentiles of travel times were predicted at the same time in one model run to facilitate easy implementation in practice.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This split could help evaluate model flexibility. GRF and QRF models were created for freeway and interchange segments separately because a previous study found the independent variables could affect these two types of segments differently ( 26 ). The 50th, 80th and 90th percentiles of travel times were predicted at the same time in one model run to facilitate easy implementation in practice.…”
Section: Resultsmentioning
confidence: 99%
“…For both GRF and QRF models, the prediction errors increase as the travel time percentile being predicted increases. The 90th percentile travel time is often used to represent the extreme situations, and past studies have found it is more challenging to predict 90th than 80th and 50th percentiles ( 26 ). Because freeway segments were longer than interchange segments and the travel times were longer, non-scaled error metrics—such as MAE, MSE, and bias—of freeway models had higher values than interchange models, but the freeway models were generally more accurate than interchange models.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations